the effect of the generative learning model on second intermediate students’ learning of deductive thinking skills in science (Journal of the College of Basic Education, 2024)
The research aims to identify the impact of the generative learning model on the second intermediate students' learning of reasoning skills in the subject of science, and by random draw method, the researcher chose a school (Al-Sana Middle School for Boys) from the research community, which is represented by secondary and middle schools of the Baghdad Governorate Directorate of Education, as the research sample included two groups, one of which represented the experimental group and the number of students (37), and the other represented the control group and the number of students (35), as the researcher adopted the experimental research method with partial control as a method for conducting the research. The researcher adopted the experimental research method with partial control as a method to conduct her research, which includes an independent variable (generative learning model) and a dependent variable (inferential thinking), as the researcher chose the experimental design to control the research variable, and before starting to apply the experiment, the researcher rewarded between the two research groups for the purpose of obtaining accurate results with the following variables: (chronological age of students calculated in months, previous knowledge of students, Danlis IQ test), and after conducting equivalence between the two research groups, the researcher prepared the application requirements of plans, objectives and a test of reasoning skills for the two research groups, and after completing the application of the experiment, the researcher applied her research tool to the two research groups, to obtain the final results by statistically processing those data through a t-test for two independent samples, as the results showed that the experimental group students outperformed the control group students in the test of reasoning skills.